First multi-proxy chronostratigraphy of the lower Cambrian Byrd Group, Transantarctic Mountains and correlation within East Gondwana - Betts, Marissa J.; Claybourn, Thomas M.; Holmer, Lars E.; Skovsted, Christian B.; Myrow, Paul M.; Stemmerik, Lars; Topper, Timothy P.; Park, Tae Yoon S.; Hughes, Nigel C.; Crowley, James L.; Jagodzinski, Elizabeth A.; Brock, Glenn A. (Gondwana Research, 2024)
Antarctica and Australia were sutured together at the equator during the major pulse of animal biodiversification associated with the Cambrian radiation. However, the lack of detailed systematic chemostratigraphic and biostratigraphic sampling of lower Cambrian sedimentary successions from Antarctica has significantly impeded precise age determination and correlation with Cambrian strata on other palaeocontinents. This study is the first to present integrated, simultaneously sampled biostratigraphic and chemostratigraphic (δ 13 C isotopes) data from the same measured stratigraphic sections through the lower Cambrian Byrd Group in the Transantarctic Mountains. Shelly fossil assemblages (brachiopods, tommotiids, molluscs, bradoriids, trilobites) from the Holyoake Range and Churchill Mountains facilitate direct correlation with the Dailyatia odyssei Zone of South Australia (Cambrian Stages 3–4), and trilobites provide strong correlation between the Starshot Formation and the Cymbric Vale Formation in western New South Wales. A new ID-TIMS radiometric date of 514.96 ± 0.16 Ma from a tuff in the lower Cymbric Vale Formation is similar to dates from tuff beds in the Third Plain Creek Member of the Mernmerna Formation in the Flinders Ranges, providing an important absolute-age tie point between these lower Cambrian successions. Chemostratigraphic data from the upper Shackleton Limestone in the Holyoake Range capture a negative δ 13 C excursion that can be correlated to negative values within the multi-peaked MICE (cycles V–VIII in Siberia). Integrated faunal and chemostratigraphic data indicate a Cambrian Stages 3–4 age, giving robust chronostratigraphic context for the upper Shackleton Limestone–Holyoake Formation–Starshot Formation succession for the first time, permitting reconstruction of the depositional history of the lower Cambrian of Antarctica and global correlation of Byrd Group strata.